Investing in Habope : Financial Assessment of Community-Based Small Investments in Sierra Leone - World Bank (Washington, DC, 2015)
In countries ravaged by a history of civil war and genocide, the overarching goal for local government and international donors alike is to promote social cohesion, stability and community reconstruction. In Sierra Leone, reconstruction programs emphasize a decentralized approach to: (i) rapidly build market institutions; (ii) enhance community decision making; and (iii) strengthen intra and inter-community tolerance and benefit sharing. This study addresses a program to provide small grants to some of the poorest communities in Sierra Leone. The program builds on the success of relevant micro financing initiatives. However, compared to traditional loans to small enterprises, which are generally available in urban and peri-urban areas where micro financing institutions are accessible, socially motivated grants to reach the poorest households are used. This report presents the findings of financial assessments funded by the Public Private Infrastructure Advisory Facility (PPIAF) of the World Bank. The assessments cover two of the poorest districts in northern Sierra Leone under the Habope project. The project, which means ‘to give hope’ in the local language Krio, is implemented by the governments National Commission for Social Action (NaCSA) and financed by the Japan Social Development Fund (JSDF). One of its components provides grants to group enterprises which are comprised of vulnerable households who are at risk for hunger and deprivation.